A relevant summation

Calculus Level 5

1 ( 1 ) ( 2 ) ( 3 ) + 2 ( 4 ) ( 5 ) ( 6 ) + 3 ( 7 ) ( 8 ) ( 9 ) + 4 ( 10 ) ( 11 ) ( 12 ) + \large\displaystyle\dfrac{1}{(1)(2)(3)}+\dfrac{2}{(4)(5)(6)}+\dfrac{3}{(7)(8)(9)}+\dfrac{4}{(10)(11)(12)}+\ldots

Let S \large S denote the value of series above. Find the value of 10000 S \large\lfloor10000S\rfloor .


The answer is 2015.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Akiva Weinberger
May 17, 2015

Note that 0 1 x n 1 d x = 1 n \displaystyle\int_0^1x^{n-1}\operatorname d\!x=\frac1n .

Start by doing partial fractions, and then convert it to an integral and simplify.

n = 1 n ( 3 n 2 ) ( 3 n 1 ) ( 3 n ) = 1 3 n = 1 ( 1 3 n 2 1 3 n 1 ) \displaystyle\sum_{n=1}^\infty\frac n{(3n-2)(3n-1)(3n)}=\frac13\sum_{n=1}^\infty\left(\frac1{3n-2}-\frac1{3n-1}\right) n = 1 n ( 3 n 2 ) ( 3 n 1 ) ( 3 n ) = 1 3 n = 1 0 1 ( x 3 n 3 x 3 n 2 ) d x \displaystyle\phantom{\sum_{n=1}^\infty\frac n{(3n-2)(3n-1)(3n)}}=\frac13\sum_{n=1}^\infty\int_0^1(x^{3n-3}-x^{3n-2})\operatorname d\!x
n = 1 n ( 3 n 2 ) ( 3 n 1 ) ( 3 n ) = 1 3 0 1 n = 1 ( x 3 n 3 x 3 n 2 ) d x \displaystyle\phantom{\sum_{n=1}^\infty\frac n{(3n-2)(3n-1)(3n)}}=\frac13\int_0^1\sum_{n=1}^\infty(x^{3n-3}-x^{3n-2})\operatorname d\!x
n = 1 n ( 3 n 2 ) ( 3 n 1 ) ( 3 n ) = 1 3 0 1 ( 1 x 3 1 x 2 ) n = 1 x 3 n d x \displaystyle\phantom{\sum_{n=1}^\infty\frac n{(3n-2)(3n-1)(3n)}}=\frac13\int_0^1\left(\frac1{x^3}-\frac1{x^2}\right)\sum_{n=1}^\infty x^{3n}\operatorname d\!x
n = 1 n ( 3 n 2 ) ( 3 n 1 ) ( 3 n ) = 1 3 0 1 ( 1 x 3 1 x 2 ) x 3 1 x 3 d x \displaystyle\phantom{\sum_{n=1}^\infty\frac n{(3n-2)(3n-1)(3n)}}=\frac13\int_0^1\left(\frac1{x^3}-\frac1{x^2}\right)\frac{x^3}{1-x^3}\operatorname d\!x
n = 1 n ( 3 n 2 ) ( 3 n 1 ) ( 3 n ) = 1 3 0 1 1 x 2 + x + 1 d x \displaystyle\phantom{\sum_{n=1}^\infty\frac n{(3n-2)(3n-1)(3n)}}=\frac13\int_0^1\frac1{x^2+x+1}\operatorname d\!x


The antiderivative happens to be 2 3 arctan ( 2 x + 1 3 ) \frac2{\sqrt3}\arctan(\frac{2x+1}{\sqrt3}) .

n = 1 n ( 3 n 2 ) ( 3 n 1 ) ( 3 n ) = π 9 3 \displaystyle\sum_{n=1}^\infty\frac n{(3n-2)(3n-1)(3n)}=\boxed{\displaystyle\frac\pi{9\sqrt3}}

Moderator note:

This problem would be much harder if it were asked to find the exact form of S S . Wonderful!

@Pi Han Goh

Honestly , I was busy on Google Plus chatting with @Trevor Arashiro and @Sharky Kesa and others that I forgot about posting a solution here .

The method used is pretty obvious . This problem uses the same method too .

Don't worry , I'll post a solution if I say so . It's just that I honestly forgot , if you want you can cross-check with Trevor and Sharky .

Brock Brown
May 18, 2015

Python 2.7:

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
from fractions import Fraction as frac
from math import floor
a = 1
b = 1
S = 0
infinity = 2000
while a <= infinity:
    print a,b,b+1,b+2
    S += frac(a,b*(b+1)*(b+2))
    a += 1
    b += 3
print "Answer:", floor(10000*S)

Kunal Gupta
May 16, 2015

The Title Says it ALL

Moderator note:

Please refrain from posting solution with no relevant working.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...